HUBUNGAN KESEJAHTERAAN GURU DENGAN ETOS KERJA GURU PAK DI SMA/SMK TAHUN 2019 - Epiphanias Estomihi Rajagukguk (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2019)
vAbstract, The purpose of the study to determine the relationship of teacher welfare with the work ethicof Christian Education teachers in North Tapanuli Regency in 2019. The population was all ChristianEducation teachers in North Tapanuli District in 2019, which totaled 289 people. The sample wasdetermined by a purposive sampling technique (aiming at sampling techniques) by establishingChristian Education teachers who taught at the high school / vocational high school level in NorthTapanuli District, amounting to 30 teacher. Data was collected with a closed questionnaire instrument.The results of the analysis of the value of rxy = 0.643 rtable = 0.361 indicate that there is arelationship between the welfare of teachers and the work ethic of Christian Education teachers inNorth Tapanuli Regency in 2019 with a strong category. Hypothesis test is obtained t = 4.443 table =2.048 with the hypothesis. The research is that there is a positive and significant relationship betweenthe welfare of teachers and the work ethic of Christian Education teachersKeywords: Teacher Welfare, PAK Teacher Ethos